The case of primary ovarian ectopic - Undinti, Nagashree; Charumathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Ovarian ectopic pregnancy is a rare form of ectopic pregnancy. It mimics tubal ectopic, difficult to distinguish on ultrasound imaging and clinical presentation. It mostly presents with rupture in first trimester. We presented this case in view of its varied tricky clinical presentation- which lead us into various differential diagnoses for pain abdomen and the least suspicion of an ovarian pregnancy. Laparoscopic management is needed for diagnosis and confirmation is only through a histopathological diagnosis. Even though it’s rare, still we need to be suspicious of this in all patients with acute lower abdominal pain and with no period of amenorrhoea.